2020
DOI: 10.1177/1075547019898256
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Misperceptions: The Causal Role of Motivation in Corrective Science Communication About Vaccine and Food Safety

Abstract: Some people stick to beliefs that do not align with scientific consensus when faced with science communication that contradicts those misperceptions. Two preregistered experiments (total N = 1,256) investigated the causal role of motivated reasoning in the effectiveness of correcting misperceptions. In both experiments, accuracy-driven reasoning led to a larger corrective effect of a science communication message than reasoning driven by directional motivation. Individuals’ default reasoning made them just as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Communicating the facts would thus result in large scale polarization. In contrast, the findings of this meta-analysis are in line with other recent work (e.g., Nyhan, 2021;Swire-Thompson et al, 2020;van Stekelenburg et al, 2020;Wood & Porter, 2019), showing that communicating accurate (corrective) information, in this case information regarding agreement among scientists, is a viable strategy to inform the public.…”
Section: Discussionsupporting
confidence: 90%
“…Communicating the facts would thus result in large scale polarization. In contrast, the findings of this meta-analysis are in line with other recent work (e.g., Nyhan, 2021;Swire-Thompson et al, 2020;van Stekelenburg et al, 2020;Wood & Porter, 2019), showing that communicating accurate (corrective) information, in this case information regarding agreement among scientists, is a viable strategy to inform the public.…”
Section: Discussionsupporting
confidence: 90%
“…Also, in the context of fake claims, it has been shown that explicit instructions to engage in evaluative thinking (by prompting people to act as fact-checkers) help people identify inaccuracies in information (Brashier et al, 2020). Furthermore, research shows that correcting misperceptions by exposing people to science communication is most effective when they are motivated to accurately process the presented information (Van Stekelenburg et al, 2020).…”
Section: The Mediating Role Of Discernment Accuracymentioning
confidence: 99%
“…Indeed, recent research shows that, when key (directional) motivations are activated before a message, people process the message in a way that is consistent with that motivation (Bayes et al, 2020). However, as the current findings indicate, it appears that people are usually motivated to be accurate and update their views in the direction of the message (van Stekelenburg et al, 2020).…”
Section: Discussionmentioning
confidence: 82%